Endurance training improves plasma superoxide dismutase activity in healthy elderly. (January 2020) - Ceci, Roberta; Duranti, Guglielmo; Di Filippo, Ester Sara; Bondi, Danilo; Verratti, Vittore; Doria, Christian; Caporossi, Daniela; Sabatini, Stefania; Dimauro, Ivan; Pietrangelo, Tiziana
Graphical abstract: MVC: isometric Maximal Voluntary Contraction; HS: Handgrip Strength; FTTST: Five Times Sit-to-Stand Test; TUG: Timed Up-and-Go test; FT: Free Thiols; SOD: total Superoxide Dismutase; MDA: Malondialdehyde: CAT: Catalase; GSH: reduced Glutathione; GSSG: oxidized Glutathione; GPx: Glutathione Peroxidase; TAS: Total Antioxidant Status; PC: Protein Carbonyl groups. Highlights: The endurance training using cycloergometer increased plasma SOD activity and handgrip strength in elderly. This effect on strength and redox homeostasis could be linked to the Bottom-Up Rise Strength Transfer (BURST) phenomenon. Abstract: We aimed to characterize the plasma redox homeostasis as underlying physiological mechanisms of specific training on healthy elderly. 51 healthy volunteers were trained to endurance, resistance, Neuro-Muscular Electrical Stimulation for 12 weeks, 3 sessions/w, all applied to lower limbs. We assessed ex-post quadriceps' maximal voluntary contraction, handgrip strength, five-times-sit to stand and timed up-and-go tests, oxidative damage (lipid peroxidation, protein carbonyl groups), antioxidant enzyme activities (superoxide dismutase, Catalase, Glutathione peroxidase, Glutathione homeostasis), free thiols and total antioxidant status. We found significant difference in ex-post × protocol and in post-hoc analysis specifically for plasma superoxide dismutase activity in endurance training.